Особенности расчета магнитных систем с короткозамкнутыми вторичными обмотками в плоскопараллельной постановке - Байда, Е.И. (Електротехніка і електромеханіка, 2015)
В статье анализируются проблема, связанная с вопросами корректного задания первичных источников токов и ошибок в определении параметров вторичных короткозамкнутых контуров при решении задач плоскопараллельного поля.
Приводятся физический и математический анализ ошибки и предложен способ решения подобных задач на примере
расчета трансформатора тока и электромагнита переменного тока. У статті аналізуються проблема, пов'язана з питаннями коректного завдання первинних джерел струмів і помилок у
визначенні параметрів вторинних короткозамкнених контурів при вирішенні задач плоскопараллельного поля. Наводяться фізичний і математичний аналіз помилки та запропоновано спосіб вирішення подібних завдань на прикладі
розрахунку трансформатора струму і електромагніту змінного струму. Introduction. A feature of quasi-static calculation of plane electromagnetic fields is unlimited volume occupied by the current.
This condition imposes certain requirements on the choice of
boundary conditions for solving such problems (the vanishing of
the algebraic sum of the currents flowing through the cross section of all wires), failure of which leads to incorrect results.
Purpose. The mathematical formulation of the boundary conditions corresponding to real physical processes in solving problems of plane quasi-static field by Kelvin transformation and
development of a technique for calculating the induced currents
in closed circuits in the calculation of AC electromagnet in the
quasi-static mode. Methods. Investigation of nonlinear model of
the current transformer in in-plane electromagnetic field calculation and the AC electromagnet is carried by the finite element
method using a specific software package. Results. A possible
error in the boundary conditions and summarizes the estimated
model corresponds to the physics of the process using the Kelvin
transform, proposed method of calculating currents in closed
loop AC electromagnet in the calculation of plane problems of
the field. Conclusions. The specificity of the problem of calculating the electromagnetic field in in-plane formulation requires
a special approach to the assignment of boundary conditions
and calculation of the currents induced in a closed loop.